What Solutions Exist for Developmental Delays Facing Indigenous Children Globally? A Co-Designed Systematic Review - Macniven, Rona (Children (Basel), 2020)
Early childhood is important for future cognitive and educational outcomes. Programs overcoming barriers to engagement in early education for Indigenous children must address family cultural needs and target developmental delays. This systematic review identifies culturally adapted programs to improve developmental delays among young children, in response to an identified priority of a remote Indigenous community. Five databases (the Cochrane Library, Embase, Medline, Scopus and CINAHL) were searched for English language papers in January 2018. Study quality was assessed, and findings were analysed thematically. Findings were presented to the community at an event with key stakeholders, to determine their inclusion and face validity. Seven relevant studies, published between 1997 and 2013, were identified by the researchers and each study was supported by the community for inclusion. Three studies included on Native American children and four studies included children from non-Indigenous disadvantaged backgrounds. Findings were reported narratively across four themes: storytelling to improve educational outcomes; family involvement improved development; culturally adapted cognitive behavioural therapy to reduce trauma; rewards-based teaching to improve child attention. Limited published research on culturally adapted and safe interventions for children with developmental delays exists but these four themes from seven studies identify useful components to guide the community and early childhood program development.